If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 15 = 7 Reorder the terms: 15 + 8y = 7 Solving 15 + 8y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 8y = 7 + -15 Combine like terms: 15 + -15 = 0 0 + 8y = 7 + -15 8y = 7 + -15 Combine like terms: 7 + -15 = -8 8y = -8 Divide each side by '8'. y = -1 Simplifying y = -1
| 3x+20=x+2 | | 5x-1/6x-9-5x-10/8x^2-18=9x-4/8x-12 | | 3x+6+9=12 | | -3(4T-1)=-(t-14) | | 9h-27=36 | | 4/5x5/16 | | -5b+7-4b-2-b=-15 | | 4(3+4)-3=25 | | 2x+20=94 | | 5a+9b=360 | | 4/3T=-36 | | 4(3+4x)=25 | | 4c-8=5c+15 | | (x-7)(x+3)=24 | | 10p-7=24 | | -11.4-m=10.9 | | 20p-7=24 | | 37+(9x-1)=90 | | 3x/4-2/3=5/6 | | (3y+7)(-4x+2)= | | (6x^2+7)-(-4y^2+7)= | | 6x+15=64 | | sinx=73 | | (x+1)(10x)=(12x+2)x | | (6x+36)=(2x-5) | | 30=-3(-6-2z) | | -9x-22=-184 | | 6w^4+w^3-3w^2=0 | | 56+(7x-1)=90 | | (15/8)=((17-x)/x) | | 5n(4n+1)=0 | | 16+5a=31 |